2013
DOI: 10.1016/j.otsr.2012.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular fracture: Long-term follow-up and factors associated with secondary implantation of total hip arthroplasty

Abstract: 4; retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 59 publications
2
36
0
Order By: Relevance
“…As various previous studies had revealed, the congruency of the fracture site correlated directly with the functional outcome of displaced acetabular fractures 9,10,11 . Open reduction remains the best method to achieve good anatomical reduction, as borne out in our study.…”
Section: Discussionmentioning
confidence: 74%
“…As various previous studies had revealed, the congruency of the fracture site correlated directly with the functional outcome of displaced acetabular fractures 9,10,11 . Open reduction remains the best method to achieve good anatomical reduction, as borne out in our study.…”
Section: Discussionmentioning
confidence: 74%
“…However, in the literature, a 3.5%-21 % rate of conversions to THA 55,57,58,152,153 is reported. In our series, we showed a conversion rate of 6% after 10 years of FU.…”
Section: Secondary Total Hip Replacementmentioning
confidence: 96%
“…In our series, we showed a conversion rate of 6% after 10 years of FU. For operatively treated fractures the rate of secondary THA is higher, with reported rates between 8 % and 53% 41,42,57,73,119,136,154 . Our cohort of operatively treated fractures had a conversion rate to THA of 14% after an average FU of 11 years.…”
Section: Secondary Total Hip Replacementmentioning
confidence: 99%
“…Although some studies have evaluated patients undergoing THA after acetabular fracture at long-term followup [5,14], and others have compared THAs performed after acetabular fractures with THAs performed for other indications [11], few have reported 10-year survivorship data in a well-controlled study. The aim of this retrospective matched cohort study is to investigate the long-term survival and clinical and radiographic results in patients who have undergone THA after an acetabular fracture as compared with patients who underwent THA for primary OA or avascular necrosis (AVN).…”
Section: Introductionmentioning
confidence: 99%